Biographies for Artistic and Social Intervention: A Youth-Driven Project - Carvalho, Cláudia Pato (2014)
This article discusses how biographical materials may be used in youth arts education projects to develop new methodologies and approaches that can stimulate artistic and social intervention in contemporary urban communities, thus changing the field of arts education policy at the community level. Through their creation of Artistic Society Projects, a group of young people from the arts education project Bando à Parte: Youth Cultures, Arts and Social Inclusion (O Teatrão, Coimbra, Portugal) have created a voice that may be used to transform their own communities. The starting points for this transformation are the young peoples’ biographical paths. The influence of youth on education policy may be strategically understood in the context of formal and nonformal school curricula. How can youth use their biographies to develop specific contributions both to change in individual behaviors and to social change in urban communities, influencing arts education policies to instigate action? The exploration of these processes through the work of artistic creation, inspired by collected biographical materials, represents a contribution to ongoing reflection on the issues of memory, identity, youth resistance, and community change in urban settings, influencing the ways in which arts education policy is understood and implemented.